2016
DOI: 10.1002/app.44370
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity and transparency of polymer hybrid nanocomposites based on poly(trimethylene terephthalate) containing single walled carbon nanotubes and expanded graphite

Abstract: Single-walled carbon nanotubes (SWCNT)/expanded graphite (EG)/poly(trimethylene terephthalate) (PTT) hybrid nanocomposites were prepared via in situ polymerization. Raman spectroscopy and scanning electron microscopy (SEM) were employed to determine both, purity and morphology of the nanofillers and the dispersion of nanotubes and nanosheets. The electrical and optical properties of thin polymer films based on both "single" nanocomposites and hybrid nanocomposites were studied. For PTT/ SWCNT nanocomposites, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…nanocomposites Neat poly(trimethylene 2,5-furanoate) (PTF) and PTF-based nanocomposites were prepared via in situ polymerization, following the same procedure as described elsewhere for PTT based nanocomposites [41,46,50,51]. In brief, 0.1 and 0.3 wt% of FLG was dispersed in 200 mL of bio-PDO using ultrahigh speed stirrer (Ultra-Turax T25, Wilmington, NC, USA) for 15 min, and subsequently an ultrasonicator (Homogenizer HD 2200, Sonoplus (Berlin, Germany) with frequency of 20 kHz and power 200 W) for 15 min.…”
Section: Preparation Of Neat Ptf and Polymermentioning
confidence: 99%
“…nanocomposites Neat poly(trimethylene 2,5-furanoate) (PTF) and PTF-based nanocomposites were prepared via in situ polymerization, following the same procedure as described elsewhere for PTT based nanocomposites [41,46,50,51]. In brief, 0.1 and 0.3 wt% of FLG was dispersed in 200 mL of bio-PDO using ultrahigh speed stirrer (Ultra-Turax T25, Wilmington, NC, USA) for 15 min, and subsequently an ultrasonicator (Homogenizer HD 2200, Sonoplus (Berlin, Germany) with frequency of 20 kHz and power 200 W) for 15 min.…”
Section: Preparation Of Neat Ptf and Polymermentioning
confidence: 99%
“…Electrical conductivity measurements were performed at room temperature in the frequency range from 10 −2 Hz to 10 6 Hz using a Novocontrol broadband dielectric spectrometer following the procedure previously described in previous works …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Yu et al have found that the thermal conductivity of polycarbonate was synergistically improved by the simultaneous addition of GNP and MWCNTs nanoadditives into the matrix. More recently, Paszkiewicz et al showed that by the addition of carbon‐based hybrid nanofillers to poly (trimethylene terephthalate) and its block copolymer poly (trimethylene terephthalate‐ block ‐poly (tetramethyleneoxide) (PTT‐ block ‐PTMO), one can improve the mechanical and thermal properties along with electrical and thermal conductivity of the nanocomposites. Thus, one can propose the study on the synergistic influence of hybrid nanofillers on the physical performance of PET‐G as polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…They show characteristic electric conductivity based on the conjugated pi-electron system. Accordingly, they are used in organic electronic devices [2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…To date, various polymers have been used to prepare polymer/ nanomaterial composites: for example, poly(L-lactide) [10,13], poly(trimethylene terephthalate) [11], polycarbonate/ethylene-propylene copolymer [12], polydimethylsiloxane [14], polyvinylpyrrolidone [15], etc. Many hybrid materials have been fabricated by means of physical dispersion of nanoparticles into polymers.…”
Section: Introductionmentioning
confidence: 99%